Ekhokardiografi Endokardiosis Penyakit Katup Mitral Jantung Anjing (ECHOCARDIOGRAPHY OF ENDOCARDIOSIS MITRAL VALVE HEART DISEASE IN DOGS) - Noviana, Deni; Wulandari, Retno; Wulansari, Retno (Jurnal Veteriner; Vol 14 No 1 (2013), 2013)
Endocardiosis is a disease commonly found in Pomeranian dog characterized by progressive myxomatousdegeneration of the atrio-ventricular valves especially in the mitral valve. The purpose of this study was todefine the diagnose and severeity of this disease on the Pomeranian by using brightness mode, motion mode,dan color flow Doppler echocardiography technique. Echocardiography was performed on 8 Pomeranianconsisting of 6 males and 2 females with age range of 2-14 years. Brightness mode echocardiography wasused to see the echotexture of endocardium, mitral valve, and the valve movement. The results showedendocardium thickening, along with chronic fibrosis and nodular thickening of the anterior and posteriormitral valve leaflet. Three out of seven cases showed prolapsed of the mitral valve. Motion modeechocardiography was performed in order to measure left ventricle internal dimension, myocardium thickness,fractional shortening, left atrial and aortic dimension. The results showed myocardium thickening, alongwith left atrial enlargement. Color flow Doppler echocardiography was used to confirm the mitral valveregurgitation. Three of seven cases showed the presence of regurgitation signed by turbulence color of theprolapsed mitral valve. Based on the degree of severity, scoring system used in this study, endocardiosis canbe divided into three types that are mild, moderate and severe.
Keywords: Pomeranian, mitral valve, endocardiosis, echocardiography